2021
DOI: 10.3390/plants10050886
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Exogenous Melatonin on Overcoming Salt Stress in Sugar Beets (Beta vulgaris L.)

Abstract: Melatonin has been regarded as a promising substance that enhances the abiotic stress tolerance of plants. However, few studies have devoted attention to the role of melatonin in improving salt tolerance in sugar beets. Here, the effects of different application methods (foliar application (100 μM), root application (100 μM), and combined foliar and root application) of melatonin on the morphological and physiological traits of sugar beets exposed to salt stress were investigated. The results showed that melat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 74 publications
6
45
0
Order By: Relevance
“…An increase in root H + -pump activity could increase Na + exclusion and increase K + uptake [ 12 ]. Strong evidence has demonstrated that MT increases the root H + -pump activity, thereby promoting Na + efflux and K + influx as well as maintaining the K + /Na + ratio [ 34 ]. The observed increases in H + -ATPase activity caused by SA and MT could be attributed to the fact that SA and MT may operate directly as an antioxidant to scavenge ROS or indirectly by triggering antioxidant responses [ 9 , 19 , 21 ] ( Table 2 and Figure 6 a–c).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in root H + -pump activity could increase Na + exclusion and increase K + uptake [ 12 ]. Strong evidence has demonstrated that MT increases the root H + -pump activity, thereby promoting Na + efflux and K + influx as well as maintaining the K + /Na + ratio [ 34 ]. The observed increases in H + -ATPase activity caused by SA and MT could be attributed to the fact that SA and MT may operate directly as an antioxidant to scavenge ROS or indirectly by triggering antioxidant responses [ 9 , 19 , 21 ] ( Table 2 and Figure 6 a–c).…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [136] also reported that seed priming with MT reduces the accumulation of H2O2 and MDA and the percentage of EL and enhances the germination rate under salt stress conditions. Furthermore, Zhang et al [137] observed that both foliar and root application of MT (100 µM) increased SOD, POD, CAT and APX activities under salt stress and decreased H2O2, O2•− and MDA accumulation in Beta vulgaris. AsA content reduced by 70%, whereas an increase in GSH (305%) and GSSG (353%) contents was noticed.…”
Section: Antioxidant Defense System In Plants Under Salinitymentioning
confidence: 99%
“…Melatonin represents the earliest phylogenetic indole substance found in entire biota [ 9 , 13 , 28 ], at 0.1 pg g −1 (FW) to 20~30 µg g −1 (FW) [ 29 ]. Since 1995, it was initially detected in vascular plants, and the assimilation processes and metabolic occupations have been largely recognized [ 28 , 30 ]. This examination twisted the awareness for Mt as a potential efficient feature to motivate stress tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…This examination twisted the awareness for Mt as a potential efficient feature to motivate stress tolerance. The Mt function in plants within a stressful environment is not completely implicit, and it introduces an enthusiastic calculation, whether it performs as an antioxidant and/or plant promoter [ 12 , 28 , 31 , 32 ]. The advantageous function of Mt in stress lessening is generally attributable to elevated photosynthesis, enhancement of redox homeostasis, mitigation of oxidative burst, and regulation of the stress-responsive gene expression implicated in signal transduction [ 9 , 11 , 30 ].…”
Section: Introductionmentioning
confidence: 99%